On guilt the force shaping character, history, and culture - Carroll, John 1944- (Morality, society and culture, 2020)
Guilt is the dark force behind haunting anxiety, obsessive-compulsive behaviour, life meaninglessness, and depression– a force to be kept in check. Yet guilt is equally our richest and most hidden resource, the essence of our humanness, and it drives us on to our highest achievements. Today, when individuals feel bad it is not usually because of something specific they have done. Rather, thundering around in the depths of their being is guilt: obscure, unconscious, yet irrepressible and ever-present. Where does it come from, what are its ways, and how might it be put to useful work? This book explores the nature of guilt, shedding light on how the modern West came increasingly to understand it as ‘the most terrible sickness’. It traces the psychological origins of guilt in each person’s family, and demonstrates the historical rise of guilt in parallel with civilization. It examines the modern predicament: the difficulty of finding explanations for guilt in a secular, post-church society– and the possibility of relief from its curse, while channelling it into a fulfilling life. As such it will appeal to those with interests in sociology, psychology, psychiatry, cultural studies, cultural history, and anthropology